Histone Acetylation in the Epigenetic Regulation of Bone Metabolism and Related Diseases. (17th July 2021) - Tian, Qinglu; Gao, Shiqi; Zhou, Xuedong; Zheng, Liwei; Zhou, Yachuan
Abstract : As the earliest studied epigenetic modification, acetylation has been explored a lot through the years. While bone tissue acts as an indispensable part of body, researches aimed at the relationship between the bone and acetylation became necessary. Some environmental factors like diet may affect the metabolism status that some metabolites especially nicotinamide adenine dinucleotide (NAD) were found able to regulate intracellular histone acetylation in bone metabolism. This review focuses on representing the interaction among acetylation, metabolism, and the bone. The results showed that acetylation connects a lot with bone metabolism, while the explorations about related metabolites like acetyl-CoA or different environmental exposures are still limited. Some acetylation-related therapy methods of bone diseases based on metabolic regulation or epigenetic enzymes were also reviewed.